PENGARUH MOTIVASI BELAJAR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 21 MERANGIN - Irawati; Ferinaldi; Sukur (Mat-Edukasia, 2022)
Understanding of students' mathematical concepts is still relatively low, this is known from the results of the initial test which showed that none of the students had completed. This can be seen from the motivation of students in participating in mathematics learning, students are less motivated to learn mathematics, cheat friends, and do not work on problems seriously. This research uses a quantitative approach with correlation methods. Data collection techniques in this study were questionnaires and tests. The analytical technique used to test the hypothesis is Pearson product moment correlation. To test the significance using t-test. Based on the results of data analysis, it shows that Fcount > Ftable or 53.3452 > 2.796, then H0 is rejected, meaning that there is a significant influence between learning motivation on understanding mathematical concepts of eighth grade students of SMP N 21 Merangin in the 2021/2022 academic year. Learning motivation contributes to the understanding of mathematical concepts by 69.72% while the remaining 30.28% is influenced by other factors